TI_GERICHTE 12.2009.101 vom 15. August 2009 , Lavoro - contratto collettivo dell'edilizia - interpretazione di una norma - gruista - TI Tribunale d'appello (2009)
Lavoro - contratto collettivo dell'edilizia - interpretazione di una norma - gruista